A Consensus on Taxing the Rich? Comparing Mainstream Economics, Piketty and Post-Keynesian Economics. Issue 1 (2nd January 2020) - Zorn, Nicolas; Pressman, Steven
Abstract: Over several decades, income has become increasingly concentrated at the top of the distributional pyramid in many rich countries. Raising taxes on top income earners and top wealth owners has gained traction in many policy circles as a way to reverse this inequality surge. This paper examines the views of mainstream economists, Thomas Piketty and Post-Keynesian economists concerning the impact of taxation and optimal tax policy. We show that, in terms of taxing the rich, these three perspectives have a great deal in common, but there are also many disagreements. We argue that Piketty occupies a middle ground between mainstream and Post-Keynesian economics, and there is a good deal that Piketty and these two schools can learn from one another.